Recommendations following a modified UK-Delphi consensus study on best practice for referral and management of severe asthma. Issue 1 (28th September 2021) - Jackson, David J; Butler, Claire; Chaudhuri, Rekha; Pink, Katie; Niven, Robert; Prigmore, Samantha; Renwick, Charlotte; Calvert, James
Abstract : Introduction: Severe asthma affects an estimated 3%–5% of people with asthma and is associated with frequent exacerbations, poor symptom control and significant morbidity from the disease itself, as well as high dose of inhaled and systemic steroids used to treat it. The introduction of specialist asthma services across the UK has attempted to improve quality of care and ensure that patients undergo a full systematic assessment prior to initiation of advanced biological therapies. However, improvements are required in the patient pathway to minimise avoidable harm. Objectives: To define standards of care in areas where the evidence base is lacking through patient and healthcare professional (HCP) consensus. Methods: The precision UK National Working Group of asthma experts identified 42 statements formed from 7 key themes. An online four-point Likert scale questionnaire was sent to HCPs working in asthma throughout the UK to assess agreement (consensus) with these statements; a subset of the statements formed a patient questionnaire. Consensus was defined as high if ≥75% and very high if ≥90% of respondents agreed with a statement. Results: A total of 117/197 responses (59.3% response rate) were received from severe asthma patients (n=15) and HCPs (n=102) including respiratory physicians, respiratory nurse specialists, respiratory pharmacists, specialist physiotherapists and general practitioners. Consensus was very high in 25 (60%) statements, high in 12 (29%) statements and was not achieved in 5 (12%) statements. Based on the consensus scores, the precision UK National Working Group derived 10 key recommendations. These focus on referrals from primary and secondary care, accessing specialist asthma services, homecare provision for severe asthma patients and outcome measures. Conclusions: Implementation of these 10 recommendations across the severe asthma pathway in the UK has the potential to improve outcomes for patients by reducing delays to assessment and initiation of advanced phenotype-specific therapies.